Re-Imagining Care for Older Adults with Heart Failure and Other Serious Illnesses - Kieran Quinn, Sarina R. Isenberg, Susanna Mak and Leah Steinberg (Healthcare Quarterly, 2023)
Most patients with heart failure prefer to die at home and want to avoid unnecessary or aggressive treatments as they approach the end of life. Collaborative care models that provide coordinated, linked services from palliative and subspecialty practitioners may enable more effective heart failure–specific palliation in the home setting. Using both administrative health data at ICES and qualitative data from interviews with cardiology and palliative care physicians and nurse practitioners, researchers have found new evidence that collaborative care integrated into a regionally organized system of palliation positively impacts outcomes for people with heart failure and meets quality indicators for end-of-life heart failure care across Ontario.
Keywords: ICES, palliative care, heart failure, older adults, cardiology, chronic conditions, person-centred care, shared decision making